2022
DOI: 10.3390/ani12233388
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Structural Evolution of Porcine Epidemic Diarrhea Virus

Abstract: To analyze the evolutionary characteristics of the highly contagious porcine epidemic diarrhea virus (PEDV) at the molecular and structural levels, we analyzed the complete genomes of 647 strains retrieved from the GenBank database. The results showed that the spike (S) gene exhibited larger dS (synonymous substitutions per synonymous site) values than other PEDV genes. In the selective pressure analysis, eight amino acid (aa) sites of the S protein showed strong signals of positive selection, and seven of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Adaptive mutations at these three positively selected sites may enhance viral infectivity, help the virus evade host immunity, and enable continual environmental adaptation ( Ao, 2020 ). A study conducted in 2022 on the evolution of the molecular structure of PEDV confirmed the presence of these three positively selected nucleic acid sites and their impact on virus virulence ( Huang et al, 2022 ).…”
Section: S Protein Genetic Variationmentioning
confidence: 94%
See 1 more Smart Citation
“…Adaptive mutations at these three positively selected sites may enhance viral infectivity, help the virus evade host immunity, and enable continual environmental adaptation ( Ao, 2020 ). A study conducted in 2022 on the evolution of the molecular structure of PEDV confirmed the presence of these three positively selected nucleic acid sites and their impact on virus virulence ( Huang et al, 2022 ).…”
Section: S Protein Genetic Variationmentioning
confidence: 94%
“…Adaptive mutations at these three positively selected sites may enhance viral infectivity, help the virus evade host immunity, and enable continual environmental adaptation (Ao, 2020). A study conducted in 2022 on the evolution of the molecular structure of PEDV confirmed the presence of these three positively selected nucleic acid sites and their impact on virus virulence (Huang et al, 2022). Cheng et al (2023) amplified the S1 gene sequence of 11 PEDV endemic strains isolated from Zhejiang from 2015 to 2017 by RT-PCR and compared the amino acid sequence variations of the S1 protein.…”
Section: S Protein Genetic Variationmentioning
confidence: 99%
“…Predicting the interactions between TLR‐3 (PDB ID: 2A0Z) as a receptor and the candidate vaccine proteins as a ligand was made using the server pyDockWEB (https://life.bsc.es/pid/pydockweb; Access:2023.02). The computer software LigPLot+ was used to determine the interface between the vaccine ligand and TLR‐3 receptor and whether there are hydrogen bonds and hydrophobic interaction between amino acid residues 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…The computer software LigPLot+ was used to determine the interface between the vaccine ligand and TLR‐3 receptor and whether there are hydrogen bonds and hydrophobic interaction between amino acid residues. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…The first reported porcine epidemic diarrhea (PED) outbreak occurred in 1971 in UK pig herds [ 6 , 7 ]. Before 2010, PEDV was effectively controlled through the use of the CV777 vaccine [ 8 ].…”
Section: Introductionmentioning
confidence: 99%